Reading Your Counterpart: The Benefit of Emotion Recognition Accuracy for Effectiveness in Negotiation - ELFERBEIN, Hillary Anger (Institutional Knowledge at Singapore Management University, 2010)
Using meta-analysis, we find a consistent positive correlation between emotion recognition accuracy (ERA) and goal-oriented performance. However, this existing research relies primarily on subjective perceptions of performance. The current study tested the impact of ERA on objective performance in a mixed-motive buyer-seller negotiation exercise. Greater recognition of posed facial expressions predicted better objective outcomes for participants from Singapore playing the role of seller, both in terms of creating value and claiming a greater share for themselves. The present study is distinct from past research on the effects of individual differences on negotiation outcomes in that it uses a performance-based test rather than self-reported measure. These results add to evidence for the predictive validity of emotion recognition measures on practical outcomes.